Implementation of the Independent Curriculum to Improve Students' Literacy and Numeracy Competencies - Aries Denta Putra (Indonesia Journal of Engineering and Education Technology (IJEET), 2025)
This study aims to analyze the effectiveness of the implementation of the Independent Curriculum in improving students' literacy and numeracy competencies through a learner-centered learning approach. The Independent Curriculum emphasizes learning flexibility, differentiated teaching strategies, and the application of project-based learning relevant to students' life contexts. This study used a quantitative approach with a survey design and comparative analysis of student literacy and numeracy achievements in several schools that have implemented the Independent Curriculum for one academic year. Data were obtained through literacy and numeracy competency tests, observations of the learning process, and questionnaires for teachers and students. The results showed a significant increase in students' reading comprehension, information analysis, and contextual numerical problem-solving skills after the curriculum was implemented. Key factors supporting competency improvement include the implementation of diagnostic assessments, the use of contextual learning methods, and the increased role of teachers as learning facilitators. In addition, the project to strengthen the Pancasila Student Profile also encouraged active student involvement in the learning process. However, the study also identified challenges in terms of teachers' readiness to design differentiated learning and limited support for innovative learning resources. Therefore, it is necessary to improve teacher competency through ongoing training and school policy support so that the implementation of the Independent Curriculum can run optimally and sustainably in improving the quality of student literacy and numeracy as basic competencies for the 21st century.